Concept of Primary Care Clinic Facilities and Management in the New Era of Covid-19 - Trevino A Pakasi; Dhanasari Vidawati Trisna; Levina Stephanie Pakasi (Faculty of Medicine, Public Health, and Nursing, 2020)
This is a concept paper of how a primary clinic should be managed in the new normal era, facing the pandemic of Covid-19, but also the possible pandemic in the future. We proposed how to manage the clinic based on several findings regarding epidemiology, virus transmission, and many other best practices to reduce contact but maintaining the service through an online connection. We also highlighted the recommended use for indoor air quality management, which is the use of a HEPA filter. Other devices may be used but in special precaution.